Computational modeling of tracheal angioedema due to swelling of the submucous tissue layer. (9th March 2017) - Gou, Kun; Pence, Thomas J.
Abstract: Angioedema is a tissue‐swelling pathology due to rapid change in soft tissue fluid content. Its occurrence in the trachea is predominantly localized to the soft mucous tissue that forms the innermost tracheal layer. The biomechanical consequences, such as airway constriction, are dependent upon the ensuing mechanical interactions between all of the various tissues that comprise the tracheal tube. We model the stress interactions by treating the trachea organ as a three‐tissue system consisting of swellable mucous in conjunction with nonswelling cartilage and nonswelling trachealis musculature. Hyperelastic constitutive modeling is used by generalizing the standard anisotropic, incompressible soft tissue framework to incorporate the swelling effect. Finite element stress analysis then proceeds with swelling of the mucous layer providing the driving factor for the mechanical analysis. The amount of airway constriction is governed by the mechanical interaction between the three predominant tissue types. The detailed stress analysis indicates the presence of stress concentrations near the various tissue junctions. Because of the tissue's nonlinear mechanical behavior, this can lead to material stiffness fluctuations as a function of location on the trachea. Patient specific modeling is presented. The role of the modeling in the interpretation of diagnostic procedures and the assessment of therapies is discussed. Abstract : This article models tracheal angioedema (swelling) using an advanced hyperelastic theory incorporated with swelling.The deformation is solely caused by internal swelling. We have various levels of modeling considering the trachea to be idealized symmetric, non‐symmetric with trachealis on the back side, and patient‐specific. All these different models help us understand tracheal angioedema more profoundly. The patient‐specific modeling supplies a more realistic understanding of the tracheal angioedema, and assists corresponding clinical treatment.